1980
DOI: 10.1093/ajcp/73.6.816
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid Tumor of the Middle Ear

Abstract: A primary tumor of the middle ear with histologic, histochemical, and ultrastructural features of a neuroendocrine neoplasm is described. This neoplasm superficially resembles the so-called adenomatous tumor of the middle ear, and potential relationships and differences between these tumors are discussed. Although the histogenesis of the carcinoid tumor of the middle ear is not well understood, it most likely originates from pre-existing neuroendocrine cells or a primitive precursor cell. This neoplasm should … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0
4

Year Published

1992
1992
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(63 citation statements)
references
References 0 publications
3
56
0
4
Order By: Relevance
“…Middle ear adenoma was recognized as a distinctive ''adenomatous'' lesion separate from adenocarcinomas of the middle ear by Hyams and Michaels in 1976 [43]. Although some microscopic similarities of these tumors to ''carcinoids'' had been observed by Fayemi and Toker [43], it was until 1980 that Murphy et al [44] documented argyrophilic granules and neurosecretory-type granules in one of these neoplasms in a manuscript entitled ''Carcinoid Tumor of the Middle Ear''. Following these publications, numerous case reports and small series using immunohistochemistry and electron microscopy have confirmed a mixed or dual exocrine and neuroendocrine differentiation in these neoplasms [45][46][47][48][49][50].…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
“…Middle ear adenoma was recognized as a distinctive ''adenomatous'' lesion separate from adenocarcinomas of the middle ear by Hyams and Michaels in 1976 [43]. Although some microscopic similarities of these tumors to ''carcinoids'' had been observed by Fayemi and Toker [43], it was until 1980 that Murphy et al [44] documented argyrophilic granules and neurosecretory-type granules in one of these neoplasms in a manuscript entitled ''Carcinoid Tumor of the Middle Ear''. Following these publications, numerous case reports and small series using immunohistochemistry and electron microscopy have confirmed a mixed or dual exocrine and neuroendocrine differentiation in these neoplasms [45][46][47][48][49][50].…”
Section: The 2005 World Health Organization (Who)mentioning
confidence: 99%
“…There have been several publications dealing with so-called carcinoid tumors of the middle ear (25)(26)(27)(28)(29). It seems clear that these lesions are better interpreted as middle ear adenomas (MEA).…”
Section: "Carcinoid" Of the Middle Earmentioning
confidence: 99%
“…3 The spectrum of differentiation depends on the exocrine (mucinous) and/or neuroendocrine components defined by histologic and immunohistochemical examination. 5 It is believed that the different names given to the neuroendocrine lesions of the middle ear (carcinoid tumor, 6 adenoma, 1,2 , adenomatous tumor of the middle ear, 2 low-grade adenocarcinoma, 7 monomorphic adenoma and ceruminoma 8 ) represent the same tumor with different degrees of glandular and neuroendocrine differentiation. 3 Torske and Thompson 3 have suggested that carcinoids and adenomas of the middle ear are the same tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Others believe that middle ear carcinoid has metastatic potential, so it should be considered as a low-grade malignancy. 6,4 The differential diagnosis of benign tumors of the middle ear includes middle ear adenoma, paraganglioma, schwannoma, retrotympanic vascular masses, ceruminal gland adenomas, endolymphatic sac tumor, schneiderian-type mucosal papilloma, and lipoma. However, one should also include meningioma, which extends to the middle ear; chronic otitis media; acquired cholesteatoma; and epidermoid.…”
mentioning
confidence: 99%